Dampak Pembiayaan Kredit Usaha Rakyat (KUR) Terhadap Return on Asset (ROA) Pada BRI Syariah Periode 2019-2023 - Ropik Yunus, Dede; Supriyanto, Dodi; Hasanah, Nurul (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
One way the government supports the development of UMKM is by making it easier for UMKM players to obtain capital loan assistance. In implementing this easy financing, the government assigned various banks to distribute it, including BRI Syariah. The aim of this research is to review (1) the growth of people's business credit (KUR) during the 2019-2023 period, (2) return on assets (ROA), and (3) analyze the effect of KUR financing on ROA. Descriptive and verification methods are the methods used in this research, where the data used is secondary data from BRI Syariah financial reports for the 2019-2023 period, as well as primary data through literature study and documentation. The classical assumption test, linear regression, correlation coefficient and coefficient of determination are statistical tools used to analyze the influence between variables, after previously carrying out the classical assumption test. The results of this research show that People's Business Credit has a positive and significant relationship with Profitability (ROA). The correlation coefficient value of 0.654 shows a strong relationship and the influence of KUR on ROA is 42.8%. This research concludes that (1) the development of KUR financing over the past 5 (five) years experienced a fluctuating graph, (2) in line with point 1, ROA growth from 2019-2023 also experienced ups and downs, so (3) KUR financing has a relationship and positive influence on ROA.